Good policy choices even when voters entertain biased beliefs: a model with endogenous valence - Ivo Bischoff; Lars-H. R. Siemers (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
In The Myth of the Rational Voter Brian Caplan shows that voters entertain systematically biased beliefs on a number of essential issues of economic policy and concludes that this leads democracies to choose bad policies. We introduce the psychological concept of mental models to address voter' naive reasoning about the economy and thereby explain the persistent bias in beliefs. Next, we develop a game-theoretical model to show that this does not automatically lead to bad policy choices. The model formalizes Caplan's thought experiment No. 4 by introducing endogenous party valence to a model of probabilistic voting. In so doing, we provide an investigation of when good policies are chosen in democracy. Based on our findings, we discuss the impact of different political institutions on economic outcomes.
Keywords: D72; D78; D83; D90; P16; 330; Voting behaviour; dynamic party competition; valence; VP-functions; biased voting